2017
DOI: 10.1016/j.ridd.2016.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Substance use among individuals with intellectual disabilities living independently in Flanders

Abstract: This study demonstrated that individuals with ID living independently use a wide range of licit and illicit substances and present divergent levels and patterns of substance use. Notwithstanding the role of personal choice in substance use, more research is needed to better understand the nature and extent of substance use and related problems, as well as the role of substance-related knowledge and attitudes in individuals with ID.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
2
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 41 publications
2
6
2
6
Order By: Relevance
“…35 However, a recent study among patients with mild/moderate intellectual disability in Belgium reported non-problematic substance use to be comparable with substance use in the general population. 36 In our study, we found that the likelihood of substance use increased with higher IQ within the 22q11DS group, although this effect was small. At present, not much is known about prevalence and risk factors for substance use in non-deleted adults with intellectual disability, 37 complicating interpretation of these findings.…”
Section: Vingerhoets Et Alcontrasting
confidence: 46%
“…35 However, a recent study among patients with mild/moderate intellectual disability in Belgium reported non-problematic substance use to be comparable with substance use in the general population. 36 In our study, we found that the likelihood of substance use increased with higher IQ within the 22q11DS group, although this effect was small. At present, not much is known about prevalence and risk factors for substance use in non-deleted adults with intellectual disability, 37 complicating interpretation of these findings.…”
Section: Vingerhoets Et Alcontrasting
confidence: 46%
“…Moreover, demographic and contextual factors were of little relevance to the final models in which substance picture recognition, knowledge, attitude and modeling were added. Substance related knowledge was significantly higher in users compared to non-users of illicit substances, but not in users of licit substances, as was found in the Flemish SumID-Q study (Swerts et al 2017). For all substances, substance related positive attitudes and SU modeling were associated with an increase in SU likelihood, as previous studies in MBID found for smoking and drinking (Emerson et al 2016;Swerts et al 2017;Whitaker and Hughes 2003).…”
Section: Su Picture Recognition Knowledge Attitudes and Modeling Asupporting
confidence: 66%
“…Therefore, we assessed SU rates and risks in individuals with MBID in several Dutch ID services. In our sample, the rates of current smoking (62%), current cannabis and other illicit drug use (15%), but not drinking (64%) were very high, given the SU rates in the Dutch general population (past month tobacco use ≈ 25%, alcohol use ≈ 77%, cannabis use ≈ 5%, stimulant use <1%) (Van Laar and (Swerts et al 2017), all SU rates seem rather high, but illicit drug use in our study stands out. This may be explained by higher levels of use and willingness to disclose such use, related the Dutch cannabis policies (i.e., users are seldomly prosecuted) that mislead some individuals with MBID to think cannabis use is legal in the Netherlands (VanDerNagel et al 2013.…”
Section: Su Picture Recognition Knowledge Attitudes and Modeling Asupporting
confidence: 37%
See 1 more Smart Citation
“…[45] Recent studies among individuals with ID in Canada and Belgium reported a significantly higher prevalence of SUD compared to the general population. [67] This may be due to a relatively high risk of abuse, dependency,[8] and severe adverse consequences[9] even after initial use among these individuals. Moreover, substance use in individuals with ID is known to be a known risk factor for anxiety/depression, intrusive thoughts, and aggressive and antisocial behavior.…”
Section: Introductionmentioning
confidence: 99%